Analisis Pelayanan Keperawatan Terhadap Kepuasan Pasien di Rumah Sakit Omni Cikarang Tahun 2021 - Muhammad Irsyad; Thomson P. Nadapdap; Arifah Devi Fitriani (Pusat Riset dan Inovasi Nasional, 2024)
The study conducted at OMNI Cikarang Hospital in 2021 aimed to assess the impact of nursing services on patient satisfaction. Using a cross-sectional, analytical survey methodology, 73 respondents, comprising both inpatients and outpatients, were sampled through accidental sampling. Bivariate and univariate analysis were employed for data analysis.Results revealed that 61.6% of respondents were classified as satisfied, while 38.4% were unsatisfied. Patient satisfaction was significantly associated with tangibles, dependability, assurance, responsiveness, and empathy, as indicated by the chi-square statistical test. Particularly, there was a substantial correlation (Spearman rho = 0.799) between patient satisfaction and the responsiveness of nursing services.The findings underscored the importance of maintaining and enhancing the standard of nursing care to ensure patient satisfaction. Specifically, the study emphasized the significance of tangibles, dependability, responsiveness, assurance, and empathy in influencing patient satisfaction levels. Therefore, it is imperative for medical professionals, especially nurses, to focus on these aspects to meet patient expectations and enhance their overall experience with healthcare services.In conclusion, the study highlighted the crucial role of nursing services in shaping the perception of health service institutions like OMNI Cikarang Hospital. By prioritizing and improving various dimensions of nursing care, hospitals can strive to consistently meet patient needs and expectations, ultimately enhancing overall satisfaction levels.